1968
DOI: 10.1002/ajpa.1330290308
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hereditary factors in the blood of Indians of the Gila river, Arizona

Abstract: This paper reports the distribution of blood groups, A-B-H secretors, haptoglobins, transfenins and hemoglobin types among Indians of the Gila E v e r Valley in Arizona. Specimens were procured from the following putative full-bl~ods: 909 Pima, 37 Papago, and 124 Maricopa; and from the following known mixed-bloods: Pima-Papago 134, Pima-Maricopa 26, Pima-Other Indian 41, Pima-Caucasian 33. These 1304 samples were tested for factors in the A-B-0, M-N-S-s, P, Rh-Hr, Lutheran, Kell-Cellano, Lewis, Duffy, Kidd and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…To illustrate, there was little difficulty applying the criteria to the Pima. Of the two available reports, the data of Brown et al (1958) fail criterion 3 above when compared to the data of Matson et al (1968). Moreover, the Pima are a relatively well defined population.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…To illustrate, there was little difficulty applying the criteria to the Pima. Of the two available reports, the data of Brown et al (1958) fail criterion 3 above when compared to the data of Matson et al (1968). Moreover, the Pima are a relatively well defined population.…”
mentioning
confidence: 75%
“…Reference Matson and Swanson, 1963cMatson et al, 1968Matson and Swanson, 1964Cordova et al, 1967Matson and Swanson, 1963dCordova et al, 1967Cordova et al, 1967Blumberg et al, 1964Cordova et al, 1967Blumberg et al, 1964Corcoran et al, 1962Alfred et al, 1972aSzathmary et al, 1975Szathmary et al, 1975Niswander et al, 1970Gray and Laughlin, 1960Matson and Swanson, 1963cAllen and Corcoran, 1960Matson et al, 1968Matson and Swanson, 1965bChown and Lewis, 1955Pollitzer et al, 1970Doeblin and Mohn, 1967...…”
mentioning
confidence: 97%
“…On the basis of anthropometric and anthroposcopic data, HrdliCka could not thus discern any underlying biological tie between the Uto-Aztecan speaking Hopi and the Pima-Papago. Regarding gene frequency data, the Hopi-Tewa sample reported by Brown et al (1958) alleles (Matson et al, 1968;Niswander et al, 1970). It would be preferable to compare a greater number of loci between these UtoAztecan groups, but the differences in the MN and Rh systems are noteworthy.…”
Section: Pima Relationships With Other Southwest Indian Groups Indicamentioning
confidence: 95%
“…Hanna et al (1953) suggested the genetic make-up of the Pima differed significantly from the Papago, but this conclusion was based on variation at the ABO locus. Later studies on the Pima (Matson et al, 1968) and Papago (Niswander et al, 1970) which considered a greater number of loci showed a close genetic parallel between these groups. An analysis of anthropometric data also indicated the Pima and Papago were more similar to one another than to other Southwest native groups (Hanna, 1962).…”
Section: Pima Relationships With Other Southwest Indian Groups Indicamentioning
confidence: 96%
See 1 more Smart Citation